Risk Factors for Type 1 Diabetes Recurrence in Immunosuppressed Recipients of Simultaneous Pancreas–Kidney Transplants. Issue 1 (28th August 2015) - Vendrame, F.; Hopfner, Y‐Y.; Diamantopoulos, S.; Virdi, S. K.; Allende, G.; Snowhite, I. V.; Reijonen, H. K.; Chen, L.; Ruiz, P.; Ciancio, G.; Hutton, J. C.; Messinger, S.; et al.
Abstract : Patients with type 1 diabetes (T1D) who are recipients of pancreas transplants are believed to rarely develop T1D recurrence in the allograft if effectively immunosuppressed. We evaluated a cohort of 223 recipients of simultaneous pancreas–kidney allografts for T1D recurrence and its risk factors. With long‐term follow‐up, recurrence was observed in approximately 7% of patients. Comparing the therapeutic regimens employed in this cohort over time, lack of induction therapy was associated with recurrence, but this occurs even with the current regimen, which includes induction; there was no influence of maintenance regimens. Longitudinal testing for T1D‐associated autoantibodies identified autoantibody positivity, number of autoantibodies, and autoantibody conversion after transplantation as critical risk factors. Autoantibodies to the zinc transporter 8 had the strongest and closest temporal association with recurrence, which was not explained by genetically encoded amino acid sequence donor–recipient mismatches for this autoantigen. Genetic risk factors included the presence of the T1D‐predisposing HLA‐DR3/DR4 genotype in the recipient and donor–recipient sharing of HLA‐DR alleles, especially HLA‐DR3. Thus, T1D recurrence is not uncommon and is developing in patients treated with current immunosuppression. The risk factors identified in this study can be assessed in the transplant clinic to identify recurrent T1D and may lead to therapeutic advances. Abstract : This study demonstrates that recurrence of islet autoimmunity and type 1 diabetes is a significant cause of immune‐mediated endocrine pancreas graft function in immunosuppressed recipients of simultaneous pancreas‐kidney transplants, and defines risk factors for this condition.